Proceedings of the 2004 First Annual DG ECFIN Research Conference on "Business Cycles and Growth in Europe" - DG ECFIN Research Conference 2004 : Brussels, Belgium); Jonung, Lars.; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2005)
In October 2004, the Directorate General for Economic and Financial Affairs (ECFIN) held its first annual research conference. Its theme was "Business Cycles and Growth in Europe". The thirteen papers presented are collected here in revised form in two volumes as Economic Paper number 227, 1/2 and 2/2. Some of the contributions are followed by comments made by the discussants. The conference was subdivided into four main sessions: • Differences and commonalities in business cycles and growth: evidence from the EU and US; • International transmission of business cycles; • Business cycles in Europe; • Business cycles and growth: theory and evidence from old and new Member States. The papers presented here are printed in the order of the programme.
Economic Papers